Quadronimic interpretation of English-language digital discourse - Lazebna, Nataliia (Linguistics and Culture Review, 2021)
The paper focuses on the English-language digital discourse (EDD) and considers it in terms of Descartes’ square. Despite the incongruence of the medieval philosophical paradigm with the modern stage of posthumanitarian studies, it is the quadronymic and clearly delineated frame, “perspicuae veritates” (according to R. Descartes), which can balance a diverse phenomenon of digital discourse. There are three main aspects of the study considered further: English-language digital discourse and its quadronymic potential, which is interpreted in three main perspectives: in terms of discursive impulse and discourse response; within hyper- / hypodynamic levels of English-language digital discourse and the English-language digital textual space (EDTS). Quadrominic interpretation of English-language digital discourse results in the following findings: symmetry of discourse construction; logic and sequence of discourse representation and its parameters; slot representation of discourse paradigmatic parameters; identification of interdependencies, conditions and parameters of discourse within quadrants.